Modeling Plastic Deformation of Steel Plates in Hypervelocity Impact Experiments. (2015) - O'Toole, Brendan; Trabia, Mohamed; Hixson, Robert; Roy, Shawoon K.; Pena, Michael; Becker, Steven; Daykin, Edward; Machorro, Eric; Jennings, Richard; Matthes, Melissa
Abstract: Hypervelocity impact experiments were done with a two-stage light gas gun to study the plastic deformation of metallic plates. Cylindrical Lexan projectiles were fired at A36 steel target plates with a velocity range of 4.5-6.0 km/s. Experiments were designed to produce a front side impact crater and a permanent bulging deformation on the back surface of the target while preventing complete perforation. Free surface velocities from the back surface of target plate were acquired using the newly developed Multiplexed Photonic Doppler Velocimetry (MPDV) system. Two different computational techniques were developed to simulate this type of experiment: Lagrangian-based smooth particle hydrodynamics (SPH) in LS-DYNA and the Eulerian-based hydrocode CTH. Parameters for material models including equation of state, compressive strength, and spall model were selected to obtain highest fidelity numerical results to compare with experiment.